Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1055/a-1467-2432
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Dibenzyls by Nickel-Catalyzed Homocoupling of Benzyl Alcohols

Abstract: Dibenzyls are essential building blocks widely used in organic synthesis, and they are typically prepared by the homocoupling of halides, organometallics, and ethers. Herein, we reported an approach to this class of compounds using alcohols, which are more stable and readily available. The reaction proceeds via nickel-catalyzed and DMO-assisted dynamic kinetic homocoupling of benzyl alcohols. Both primary and secondary alcohols are tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…The Shu group has used this strategy to synthesize dibenzyls by nickel‐catalyzed direct homocoupling of benzylic alcohols (Scheme 24). [ 41 ] By utilization of Ni(dppe)Cl 2 (5 mol%) without additional nitrogen ligand, various primary benzyl alcohols were dimerized to dibenzyls. Of note, aryl chloride has been reported to couple with benzyl alcohols, and it was tolerated.…”
Section: Nickel‐catalyzed Deoxygenative Cross‐coupling Of Alcohols Wi...mentioning
confidence: 99%
“…The Shu group has used this strategy to synthesize dibenzyls by nickel‐catalyzed direct homocoupling of benzylic alcohols (Scheme 24). [ 41 ] By utilization of Ni(dppe)Cl 2 (5 mol%) without additional nitrogen ligand, various primary benzyl alcohols were dimerized to dibenzyls. Of note, aryl chloride has been reported to couple with benzyl alcohols, and it was tolerated.…”
Section: Nickel‐catalyzed Deoxygenative Cross‐coupling Of Alcohols Wi...mentioning
confidence: 99%
“…In 2021, Shu and co-workers found that dimethyl oxalate (DMO) can undergo an equilibrium reaction with alcohols, and the formed alkyl oxalates can participate in coupling reactions. They used this strategy to successfully synthesize dibenzyls by utilization of Ni­(dppe)­Cl 2 without additional nitrogen ligand . Recently, Iwasawa’s group reported a Ti–O bond photohomolysis under UV-light irradiation for generating Ti­(III) using isopropyl alcohol as a stoichiometric reductant.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The compound IV (Figure 1), owing tetra-arylethane motif, is a sunscreen-based photolabile caged molecule for controlled discharge of carbonyl compounds. 7 Numerous synthetic protocols have been demonstrated so far to access tetra-arylethane derivatives, including dehydroxylative dimerization of benzylic alcohols under visible-light irradiation, 8 nickel/oxo-rhenium-catalyzed and ReIO 2 (PPh 3 ) 2 -promoted reductive coupling of secondary benzylic alcohols, [9][10][11] dehalogenative radical coupling of secondary benzylic halides, [12][13][14][15][16] dehydrogenative homocoupling of benzylic C-H bonds under photoredox catalysis, 17 photoderiven decarboxylative radical dimerization of diphenyl acetic acid, 18 hydrogenation of tetraphenylethylene using a metal-based amide catalyst, 19 nickel-catalyzed and hydrazine-mediated deoxygenative coupling of ketones 20 and reductive coupling of aromatic ketones under photoredox conditions. 21,22 Recently, Tang, Cai and coworkers have been described a visible lightmediated potassium-modified carbon nitride (CN-K) catalyzed reductive dimerization of p-quinone methides (p-QMs) to access tetra-arylethane derivatives.…”
Section: Introductionmentioning
confidence: 99%